Flexible Prussian Blue‐Au Fibers as Robust Peroxidase – Like Nanozymes for Wearable Hydrogen Peroxide and Uric Acid Monitoring. Issue 11 (27th April 2022) - Li, Jiahui; Jiao, Lei; Xiao, Xiao; Nashalian, Ardo; Mathur, Shaurya; Zhu, Zhijun; Wu, Weitai; Guo, Weiwei; Zhai, Yanling; Lu, Xiaoquan; Chen, Jun
Abstract: Fiber‐based electronics technology has been making significant strides towards applicable emergence into many fields. One such field is the use of fiber‐based electronics in the development of smart textiles. Here, we report the use of stretchable styrene‐ethylene‐butylene‐styrene (SEBS) fibers as a conductive substrate to simultaneously load Au nanowire and Prussian blue (PB) as biosensing interfaces. Accordingly, due to the synergistic catalytic effect between Au nanowire and Prussian blue, the as‐obtained flexible PB/Au fibers can not only show the potential as wearable biosensors but also serve as high‐performance peroxidase‐like nanozymes. The functional fibers can be used for colorimetric detection of H2 O2 and uric acid, exhibiting satisfactory sensitivity and selectivity in serum sample analysis. The flexible PB/Au fibers represent a new form of Peroxidase‐like nanozymes, which could open doors to various wearable biosensing applications. Abstract :